Respuesta :

Answer: Here I hope this helps!

Step-by-step explanation:

For example lets work with this fraction

 [tex]\frac{6}{5} -\frac{3}{7}[/tex]

First you need to find a common denominator. (The number at the bottom of the fraction always.)

Multiply until you get a number both denominators go into.

For this it would be 35.

[tex]\frac{6}{5} -\frac{3}{7}[/tex]

5x7=35  7x5=35

You then have to do the same to the top as you did the bottom.

So multiply your numerators (number at the top) the same number as you did to the denominator below it.

[tex]\frac{6}{5} -\frac{3}{7}[/tex]

So 6x7=42.    

And 3x5=15

You then subtract the numerators.

42-15=27

So now you have [tex]\frac{27}{35}[/tex]

[tex]\frac{6}{5} -\frac{3}{7}[/tex] =[tex]\frac{27}{35}[/tex]

Hope this helps! Have a great day!!